KONSERVASI MASJID AGUNG KAUMAN SEMARANG SEBAGAI BENDA CAGAR BUDAYA - Hendro, Eko Punto (Paramita: Historical Studies Journal, 2011)
The efforts to the conservation of the Masjid Agung Kauman of Semarang was very important, because: first, the mosque was a historical monument which had to be preserved, and second, it is to equip the revitalization and conservation programs of the Semarang Old City as the colonial remain. The research focused on the efforts to make the mosque returned to the original form and also to detect the damages, the rotten part and the change of the components of the building, as well as the physical or the mechanistic process. The method, which has been applied in this research, was observation, photography and documentation, sample derivation, data and laboratory analyses, deciding the kind of the construction and describing the architecture. To make the mosque returned to the original form and preserve its continuance, it is necessary to reveal the models of the conservation which have based on the right rule and method. Ã‚Â  Key Word: Mosque, Conservation, Tourism